2023
DOI: 10.1146/annurev-pharmtox-051921-092701
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Antiplatelet Therapy

Abstract: Antiplatelet therapy is used in the treatment of patients with acute coronary syndromes, stroke, and those undergoing percutaneous coronary intervention. Clopidogrel is the most widely used antiplatelet P2Y12 inhibitor in clinical practice. Genetic variation in CYP2C19 may influence its enzymatic activity, resulting in individuals who are carriers of loss-of-function CYP2C19 alleles and thus have reduced active clopidogrel metabolites, have high on-treatment platelet reactivity and increased ischemic risk. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 131 publications
0
13
0
Order By: Relevance
“…The CPIC recommends with level A evidence that clopidogrel be avoided in individuals with a poor or intermediate CYP2C19 metabolizer phenotype using an alternative P2Y 12 inhibitor (e.g., ticagrelor or prasugrel) instead and that clopidogrel can be considered in individuals with a normal, rapid, or ultrarapid CYP2C19 metabolizer phenotype ( Table 3 ). 54 Results from RCTs and meta‐analyses have guided these CPIC recommendations 59 . In POPular Genetics, a genotype‐guided strategy (ticagrelor or prasugrel in all except normal, rapid, or ultrarapid CYP2C19 metabolizers who were de‐escalated to clopidogrel) was noninferior to standard‐treatment (ticagrelor or prasugrel in all) for the primary composite outcome of death, myocardial infarction (MI), stent thrombosis, stroke, or major bleeding at 12 months (5.1% vs. 5.9%, respectively; noninferiority P < 0.001) and superior to standard‐treatment in reducing the incidence for the primary bleeding outcome (9.9% vs. 12.5%, respectively, P = 0.04) in patients undergoing PCI 37 .…”
Section: Step 4: Know the Current Cardiovascular Therapies To Focus O...mentioning
confidence: 99%
“…The CPIC recommends with level A evidence that clopidogrel be avoided in individuals with a poor or intermediate CYP2C19 metabolizer phenotype using an alternative P2Y 12 inhibitor (e.g., ticagrelor or prasugrel) instead and that clopidogrel can be considered in individuals with a normal, rapid, or ultrarapid CYP2C19 metabolizer phenotype ( Table 3 ). 54 Results from RCTs and meta‐analyses have guided these CPIC recommendations 59 . In POPular Genetics, a genotype‐guided strategy (ticagrelor or prasugrel in all except normal, rapid, or ultrarapid CYP2C19 metabolizers who were de‐escalated to clopidogrel) was noninferior to standard‐treatment (ticagrelor or prasugrel in all) for the primary composite outcome of death, myocardial infarction (MI), stent thrombosis, stroke, or major bleeding at 12 months (5.1% vs. 5.9%, respectively; noninferiority P < 0.001) and superior to standard‐treatment in reducing the incidence for the primary bleeding outcome (9.9% vs. 12.5%, respectively, P = 0.04) in patients undergoing PCI 37 .…”
Section: Step 4: Know the Current Cardiovascular Therapies To Focus O...mentioning
confidence: 99%
“…Since these trials were completed, numerous studies have demonstrated that clopidogrel‐treated patients with a CYP2C19 no function allele are at increased risk of adverse cardiovascular outcomes following ACS and PCI compared to patients without a no function allele 18 . These studies have been reviewed elsewhere 18,55,56 . A meta‐analysis of data from nine trials or registries including 9685 high‐risk patients (95% had an ACS; 91% underwent PCI) with CYP2C19 data showed a higher risk for MACE among carriers of one (hazard ratio [HR], 1.55; 95% confidence interval [CI], 1.11 to 2.17) or two (HR, 1.76; 95% CI, 1.24 to 2.50) no‐function alleles compared with noncarriers 23 .…”
Section: Genetic Associations With Clopidogrel Effectiveness After Pcimentioning
confidence: 99%
“…P2Y12 inhibitors are often used for patients with CAD after percutaneous coronary intervention (PCI) in combination with aspirin (dual antiplatelet therapy/ DAPT) and for patients with ACS, with or without PCI, with guidelines recommending varying durations for secondary prevention ( 17 ). Due to genetic factors involved in CYP450 metabolic pathways, clopidogrel shows widely variable inhibition of platelet activation, with ∼30% of treated individuals categorized as poor to intermediate responders to the drug ( 18 ). Genotype-guided strategies in clopidogrel therapy have been successful ( 19 ), suggesting value in individualized pharmacogenetics as a treatment strategy in clinical practice ( 18 ).…”
Section: The Present and Future Of Antiplatelet Therapeuticsmentioning
confidence: 99%
“…Due to genetic factors involved in CYP450 metabolic pathways, clopidogrel shows widely variable inhibition of platelet activation, with ∼30% of treated individuals categorized as poor to intermediate responders to the drug ( 18 ). Genotype-guided strategies in clopidogrel therapy have been successful ( 19 ), suggesting value in individualized pharmacogenetics as a treatment strategy in clinical practice ( 18 ). Recently, the more potent and predictable ticagrelor and cangrelor have seen increasing use ( 20 ).…”
Section: The Present and Future Of Antiplatelet Therapeuticsmentioning
confidence: 99%